Lipid-modulated pharmacophore nanorods assembled at the air/water interface - Philosof-Mazor, Liron (Chemphyschem, 2009)
Biomimetic pharmacophores deposited at the air/water interface self-assemble into distinct crystalline nanostructures. The shapes and dimensions of the nanostructures are significantly modulated by the lipid environments in mixed lipid/DAG-lactone monolayers.